2017
DOI: 10.1007/s11684-016-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of blood exposure-related mental health illness among clinical nurses

Abstract: Nurses are subjected to high amount of stress in the medical setting, and work-related stress often leads to mental problems. This study aims to investigate the mental health status of nurses exposed to blood through needlestick injuries. A total of 302 nurses working in the hospital of Guangdong, China, participated in this study. Out of the 302 nurses, 140 did not experience any needlestick injuries during the previous week, whereas 162 nurses experienced needlestick injuries. The General Health Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Surgical clinics are environments with highrisk closed units such as operating rooms and intensive care units (ICUs), where critical thinking, quick decision making, and urgent interventions are intensive (Erdağı & Özer, 2015). Nurses, who are the most important members of the health care team, who provide direct care to the patient in surgical units, are exposed to numerous occupational hazards, such as drugs, chemicals, infectious agents, lack of materials and ergonomic conditions, heavy working, and excessive workload, and also they have physical (needle stinging, penetrating stab injuries, musculoskeletal disorders and pain, cancer resulting from night work, hearing loss, and varicose veins), chemical (skin problems, latex allergies), biological (infectious diseases), and psychological (stress, burnout syndrome, mental health problems, sleep disorders) problems (Anandh et al, 2015;Attar, 2014;Attarchi et al, 2014;Bernal et al, 2015;Broadwater & Brueck, 2017;Elewa & Sahar Banan, 2016;Hamnerius et al, 2018;Rathore et al, 2017;Samulin Erdem et al, 2017;Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical clinics are environments with highrisk closed units such as operating rooms and intensive care units (ICUs), where critical thinking, quick decision making, and urgent interventions are intensive (Erdağı & Özer, 2015). Nurses, who are the most important members of the health care team, who provide direct care to the patient in surgical units, are exposed to numerous occupational hazards, such as drugs, chemicals, infectious agents, lack of materials and ergonomic conditions, heavy working, and excessive workload, and also they have physical (needle stinging, penetrating stab injuries, musculoskeletal disorders and pain, cancer resulting from night work, hearing loss, and varicose veins), chemical (skin problems, latex allergies), biological (infectious diseases), and psychological (stress, burnout syndrome, mental health problems, sleep disorders) problems (Anandh et al, 2015;Attar, 2014;Attarchi et al, 2014;Bernal et al, 2015;Broadwater & Brueck, 2017;Elewa & Sahar Banan, 2016;Hamnerius et al, 2018;Rathore et al, 2017;Samulin Erdem et al, 2017;Xiong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Ganczak and Szych (2007), compliance to the use of gloves whenever was necessary accounted to 83%, while the use of double gloves in surgeries was only 12% in the survey of Jeong and colleagues in 2008 [11,12]. Furthermore, 9 studies showed that 50.9% of nurses repositioned the needle cap from a used syringe [13][14][15][16][17][18][19][20]. On the contrary, Stein et al noted that 99% of nurses reported that they cover a used needle cap and 85% reject them to special equipment [7].…”
Section: Resultsmentioning
confidence: 99%
“…Nurses have the highest rates in this type of injury than other health professionals [17].The observed high occupational exposure to pathogens among nurses could be attributed, among others, to the failure of observing safety precautions. The guidelines for nurse prophylaxis, generally, define measures concerning the organization of monitoring infections associated with health care facilities, health staff assessment on the state of vaccination, staff training in infection control and special measures for protection from blood-transmitted diseases such as the use of gloves (e.g., vaccination against hepatitis B) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers may have mental health problems such as anxiety and depression related to the work environment (58, 59). Occupational exposure has also been reported to have psychological effects (31, 60) In nurses experiencing exposure to occupational hazards, the prevalence of anxiety is higher (26), and nurses experience feelings of anxiety, anger, and guilt (60, 61). Similarly, there are similar mental problems in the studies conducted in the students (31, 62).…”
Section: Discussionmentioning
confidence: 99%
“…Because of these hazardous environments, the health of many trainees and workers are compromised each year (12, 13). Health workers may be exposed to hazardous environments and drugs such as chemotherapy drugs and gases, (1416) violence (12, 17), needlestick injuries (NSI)(1820), skin problems, latex allergies (21), musculo-skeletal system problems (back injuries) (22, 23), cancer from working at night (24), loss of hearing (25) and mental health problems (26). Especially midwifery and nursing students can experience stress (27, 28) and anxiety (29) because of their underdeveloped skills, lack of information, assignments with deadline, being exposed to occupational hazardous as other professional health workers in the clinical environment (30).…”
Section: Introductionmentioning
confidence: 99%